"Nuclear FGF Receptor‐1 and CREB Binding Protein: An Integrative Signaling Module". Issue 5 (May 2015) - Stachowiak, Michal K.; Birkaya, B.; Aletta, J.M.; Narla, S.T.; Benson, C.A.; Decker, B.; Stachowiak, E.K.
<x xml:space="preserve">Abstract</x> In this review we summarize the current understanding of a novel integrative function of Fibroblast Growth Factor Receptor‐1 (FGFR1) and its partner CREB Binding Protein (CBP) acting as a nuclear regulatory complex. Nuclear FGFR1 and CBP interact with and regulate numerous genes on various chromosomes. FGFR1 dynamic oscillatory interactions with chromatin and with specific genes, underwrites gene regulation mediated by diverse developmental signals. Integrative Nuclear FGFR1 Signaling (INFS) effects the differentiation of stem cells and neural progenitor cells via the gene‐controlling Feed‐Forward‐And‐Gate mechanism. Nuclear accumulation of FGFR1 occurs in numerous cell types and disruption of INFS may play an important role in developmental disorders such as schizophrenia, and in metastatic diseases such as cancer. Enhancement of INFS may be used to coordinate the gene regulation needed to activate cell differentiation for regenerative purposes or to provide interruption of cancer stem cell proliferation. J. Cell. Physiol. 230: 989–1002, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company